2007
DOI: 10.3844/ajptsp.2007.10.17
|View full text |Cite
|
Sign up to set email alerts
|

Aqueous Extract of Inonotus bliquus (Fr.) Pilat (Hymenochaetaceae) Significantly Inhibits the Growth of Sarcoma 180 by Inducing Apoptosis

Abstract: Inonotus obliquus (Fr.) Pilat (Hymenochaetaceae) has been widely used as a folk medicine to treat various cancers in Russia, Poland and most of Baltic countries for literally more than four centuries. However, in spite of its therapeutic significance for cancers, this fungus has not been studied systematically for the mechanisms of antitumor activity. In this study, we report the effects of aqueous extracts of I. obliquus (AEI) on inducing apoptosis of Sarcoma 180. AEI prepared from the sclerotium of I. obliqu… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
14
0

Year Published

2009
2009
2022
2022

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 28 publications
(14 citation statements)
references
References 29 publications
0
14
0
Order By: Relevance
“…Therefore, mushrooms are very attractive as a potential source of new therapeutic agents. Inonotus obliquus (Chaga mushroom), one of the well-known medicinal mushroom, has been used as remedies for gastric disorders and cancer and there are many reports published on anticancer and anti-inflammatory activities (Wasser and Weis, 1999;Hwang et al, 2003;Kim et al, 2006;Chen et al, 2007;Youn et al, 2008). In the present study, we showed that the Inonotus obliquus extract inhibits tumor cell growth of B16-F10 melanoma cells.…”
Section: Discussionmentioning
confidence: 48%
See 2 more Smart Citations
“…Therefore, mushrooms are very attractive as a potential source of new therapeutic agents. Inonotus obliquus (Chaga mushroom), one of the well-known medicinal mushroom, has been used as remedies for gastric disorders and cancer and there are many reports published on anticancer and anti-inflammatory activities (Wasser and Weis, 1999;Hwang et al, 2003;Kim et al, 2006;Chen et al, 2007;Youn et al, 2008). In the present study, we showed that the Inonotus obliquus extract inhibits tumor cell growth of B16-F10 melanoma cells.…”
Section: Discussionmentioning
confidence: 48%
“…A recent study showed that a hot water extract of Inonotus obliquus mushroom suppressed cellular proliferation of human stomach cancer cells in a time-dependent manner (Hwang et al, 2003). Also, it has been reported that the aqueous extract of Inonotus obliquus significantly inhibited the growth of Sarcoma 180 cells (Chen et al, 2007) and HepG2 cells (Youn et al, 2008). However, though Inonotus obliquus mushrooms are increasingly being used to treat a various cancer, it is relatively little knowledge of their mechanism of action (Shashkina et al, 2006).…”
Section: Introductionmentioning
confidence: 97%
See 1 more Smart Citation
“…The estimated amount of phenolic and polysaccharide delivered per mice per administration were 5.7 and 20.4 mg, respectively, for IOAE-50 mg/kg, and 11.4 and 40.8 mg for IOAE-100 mg/kg, respectively. Previous studies have reported comparatively similar values for these constituents of Chaga (Chen et al, 2007;Hu et al, 2009). The biological activities of Chaga are mainly attributed to abundantly available polar molecules like polysaccharides (Cui et al, 2005;Zhang et al, 2007), polyphenols (Cui et al, 2005;Nakajima et al, 2007), peptides (Hyun et al, 2006), and b-glucan (Rhee et al, 2008).…”
Section: Discussionmentioning
confidence: 85%
“…The biological activities oflnonotus obliquus are mainly attributed to the abundantly available molecules like polysaccharides, polyphenols, and peptides (9). Other studies have reported comparatively similar values for these constituents of lnonotus obliquus with growth inhibitory and apoptosis-inducing activity in Sarcoma 180 cells (28) and antioxidant and antiproliferative activities in DLD 1 cells (29). Although the total aqueous extract appears to be the limitation of this study, we assume that the effects of IOAE are largely ascribed to these compounds.…”
Section: Ioae Suppresses Mrna Expression Of Proinflammatory Mediatorsmentioning
confidence: 82%